Neurological symptoms occurring in the context of ruptured abdominal aortic aneurysm: a paramedic's perspective. Issue 9 (21st August 2007) - Fitzpatrick, David; Maguire, Donogh
Abstract : Ruptured abdominal aortic aneurysm (RAAA) classically presents with sudden onset, severe ripping or tearing abdominal pain radiating through to the back. This case report describes features of an atypical presentation of a patient with RAAA and highlights the difficulties and uncertainties surrounding the prehospital assessment, appropriate treatment and management of these patients. All prehospital care educators and practitioners should be made aware of the wide spectrum of clinical manifestations for this condition.